Pelaksanaan Forum Generasi Berencana Dalam Penanggulangan KenakalanRemaja Oleh Dinas Pengendalian Penduduk Keluarga Berencana, PemberdayaanPerempuan DanPerlindungan Anak Kabupaten Banyumas - Gita Nurmiana; Wahyu Hariadi; Agoes Djatmiko (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2022)
This study aims to determine how the implementation of the Generation Planning Forum in BanyumasRegency for the period 2020 - 2022 in overcoming juvenile delinquency. And how are the efforts of the localgovernment of Banyumas Regency in promoting the Banyumas Generation Planning Forum so that theprograms and objectives that have been prepared by the Banyumas Planning Generation Forum can beachieved. To achieve this goal, this study uses a sociological legal researchmethod, with the specifications ofobservational research. In this study, the data source used is secondary data which is supported by primarydata. The data presentation method in this thesis is presented in the form of a structured and systematicdescription. This research was conducted at the Department of DPPKBP3A Banyumas Regency. Based on theresults of research and discussion, it can be concluded that it can be seen that the Implementation of theGeneration Planning Forum in Banyumas Regency in tackling juvenile delinquency has been carried outproperly in accordance with the Work Program that has been formed in the Decree of the Head of the Office ofPopulation Control and Family Planning,Women's Empowerment and Child Protection. Banyumas RegencyNumber 476/497/2020, but there are several programs that have not been implemented dueto the Covid-19pandemic. The efforts of the Banyumas Regency Government in promoting the Banyumas GenerationPlanning Forum by coordinating the Banyumas Generation Planning Forum with relevant agencies, namelyall sub- districts in Banyumas Regency in the form of monitoring so that it can assist the BanyumasGeneration Planning Forum in achieving the stated goals.